Considerations for the rational design of a Chlamydia vaccine. Issue 4 (3rd April 2017) - Liang, Steven; Bulir, David; Kaushic, Charu; Mahony, James
ABSTRACT: Chlamydia trachomatis is the leading cause of preventable blindness and the most common bacterial sexually transmitted infection. Remarkable progress in vaccine research over the past six decades has led to the advancement of novel C. trachomatis vaccine candidates into clinical trials. However, many questions regarding the role of specific cellular populations and molecular mechanisms in protective immunity against human C. trachomatis genital tract infections remain unanswered. Biomarkers of vaccine induced protective immunity are elusive in humans, while a cautionary message on the translatability of data obtained from current animal models has emanated from vaccine research and development efforts against other important human pathogens. In this commentary, we highlight recent advances in Chlamydia vaccine development and discuss their implications in the context of a rational approach to the design of a human C. trachomatis vaccine.